Good Outcome of Corneal Ulcer With Hypopion After Long Use of Contact Lens - Affannul Hakim; Christina Aritonang (Vision Science and Eye Health Journal, 2023)
Introduction: Microbial keratitis is a corneal infection caused by microorganisms and is characterized by a profound corneal epithelial defect that infects the cornea and causes severe and progressive visual loss. In recent years, the incidence of microbial keratitis has increased. One of the critical risk factors for increasing this incidence is using contact lenses. As the number of contact lens users increases, the number of corneal ulcers associated with contact lenses also increases. Case Presentation: A 25-year-old man was admitted to the emergency department with a complaint of gradually blurry vision in his left eye four days after using contact lenses for overnight uses since the previous few days and did not routinely clean contact lenses or replace contact lens cleaning fluid. The visual acuity of the patient's left eye was hand movement with conjunctival and pericorneal injection in the conjunctiva and 6 x 7 mm stromal level infiltrate, blurred margin, and whitish color in the center of the cornea. After 28 days of treatment, an examination showed the patient's left eye improvement. Visual acuity was 3/60, conjunctival injection disappeared, corneal swelling significantly resolved, hypopyon disappeared, and ulcer completely re-epithelialized. Conclusions: Empirical therapy with broad-spectrum antibiotics and other adjunctive therapy has a good outcome in treating contact lens-related corneal ulcers.